PERBANYAKAN VEGETATIF SECARA CANGKOK PIPER MINIATUM BL. - Priyono, Sumarnie Hasto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Ninety percent from approximately 1200 plant species belonged to Piper genus(Piperaceae) have not been explorated their phytochemical potency and biologicalÃ‚Â activities. Piper miniatum has beeing used traditionally in Papua as spices and tonic.Ã‚Â However, the propagation effort has never been done yet so its population in nature isÃ‚Â decresed gradually. Therefore, simple propagation is conducted that can be adoptedÃ‚Â by the local people in order to cultivate as well as to explore its potency as antibacterialÃ‚Â agent. The propagation experiment was carried out using air layering method withÃ‚Â variable treatment of internode maturity ( R1, R2, R3 ), growth medium (Selaginela sp.,Asplenium nidus root, compost) with completely randomized design with 10 replications.Air layering media using Asplenium nidus root of 18 weeks gave the best respon.Key words: Piper miniatum, Air layering.